Možnosti využitia prostriedkov virtuálneho sveta vo vzdelávaní - TOLOCHKO, SVITLANA; LYMAR, VALERIIA; RIDEI, NATALIIA (Journal of Education, Technology and Computer Science, 2016)
The paper is devoted to understanding the influence of economic competitiveness and environmentalsustainability on education. It was concluded that national economic competitiveness islinked to intellectual and capital and is driven by knowledge, and innovation. Sustainable developmentrequires an understanding of the complexity of the global ecosystem and of creativeproblem-solving to find solutions to ‘wicked problems’ such as that of reconciling economicactivity with a sustainable environment. It was highlighted the following overarching needs to:give a higher profile to the notion of interdependence: how closely one part of an ecosystem islinked to and depends upon another; making humanity more aware of its own fragility on thisplanet; highlight the role of cooperation: problems faced will only be resolved by internationalcooperation; develop the notion of a global public good: environmental sustainability can only beachieved by trans ceding particular national or individual needs.